Dryas octopetala Linnaeus 1753 - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Dryas octopetala Linnaeus, Species Plantarum 1: 501. 1753. "Habitat in Alpibus Lapponicis, Helveticis, Austriacis, Sabaudicis, Hibernicis, Sibiricis." RCN: 3810. Lectotype (Barrie in Jarvis & al., Regnum Veg. 127: 44. 1993): Herb. Linn. No. 658.3 (LINN). Generitype of Dryas Linnaeus (vide Willdenow in Ges. Naturf. Freunde Berlin Mag. 5: 397. 1811). Current name: Dryas octopetala L. (Rosaceae). Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part D), pp. 474-489 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 489, DOI: 10.5281/zenodo.291971